The media and elections : a handbook and comparative study - Lange, Bernd-Peter; Ward, David, 1966- (European Institute for the Media series., 2004)
This study presents a set of national case studies and an analysis of the legal and regulatory frameworks that are employed by nation states to ensure that the media perform according to certain standards during election periods.